One phenomenon, Three perspectives. English colonial strategies in Ireland revisited, 1603-1680 - HINGST, MARIE SOPHIE (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2018)
Recent years have seen renewed scholarly interest in Ireland s position within the English colonial system during the early modern period. With regard to developments in the seventeenth century, however, the long-established narrative has identified ruptures, changes and political turmoil as the key characteristic of this period. Consequently, the question of continuities within English colonial strategies between 1603 and 1680 has not evoked much interest. This thesis wants to overcome this approach by exploring the way in which colonial policies shaped the nature of English colonialism in Ireland, while at the same time focusing on the development of long-term patterns. The completion of the Tudor conquest of Ireland in 1603 provided new momentum to the English colonial endeavour. In exploring the congruencies of renewed efforts to implement reliable governmental structures, this thesis has chosen three protagonists whose careers in Ireland offer insights into both individual strategies and continuous patterns. Examining the role of John Davies, Thomas Wentworth and William Petty allows for an examination of the distinct nature of colonial government, especially with regard to its practical implementation. Each of the selected individuals determined the practical implication of English rule in Ireland. The role of John Davies as Solicitor General in Ireland in 1608 allows insights into the emergence of colonial rule as part of a legalised political structure , in contrast to earlier strategies which were based on violent conquest and military suppression. Thomas Wentworth as Lord Deputy profoundly shaped colonial policies during the tumultuous 1630s and considered aiming to institutionalise English rule in Ireland, restructuring all aspects of colonial society in the process. William Petty, on the other hand, represents the emergence of the colonial expert in the 1650s, linking scientific elements to economic considerations. Petty s subsequent concepts, based on social engineering and the radical exploitation of Ireland, saw the beginning of a new and modern colonial vision by the late seventeenth century. This thesis argues that examining colonialism from three distinct but interlinked perspectives helps to uncover the manifold patterns and the specific contexts of colonial rule in Ireland, thus addressing the balance between change and continuity that characterised English colonial strategies during the seventeenth century.
APPROVED
Keywords: Irish History; 17th century; Early Modern History; Colonialism